Drymonia betancurii (Gesneriaceae), a new species from northwestern Colombia - Clavijo, Laura; Clark, John Littner (Phytotaxa, 2015)
A new species of Gesneriaceae from the Pacific slopes of the Colombian Andes is described and illustrated. The new species, Drymonia betancurii, is differentiated from other congeners by the following combination of characters: upper leaf surface with papillose-hispid trichomes, dark green and often covered with white spots; lower surface pitted; and corolla lobes orange-red with white to yellow margins.